Linear growth and bone metabolism in pediatric patients with inflammatory bowel disease - Paloma Velez de Andrade Lima Simões Ferreira; André de Souza Cavalcanti; Giselia Alves Pontes da Silva (Brazilian Society of Pediatrics, 2019)
Objective: To review the pathophysiology and evaluation methods of linear growth and bone mineral density in children and adolescents diagnosed with inflammatory bowel disease. Source of data: Narrative review carried out in the PubMed and Scopus databases through an active search of the terms: inflammatory bowel disease, growth, failure to thrive, bone health, bone mineral density, and children and adolescents, related to the last ten years, searching in the title, abstract, or keyword fields. Synthesis of findings: Inflammatory bowel diseases of childhood onset may present as part of the clinical picture of delayed linear growth in addition to low bone mineral density. The presence of a chronic inflammatory process with elevated serum levels of inflammatory cytokines negatively interferes with the growth rate and bone metabolism regulation, in addition to increasing energy expenditure, compromising nutrient absorption, and favoring intestinal protein losses. Another important factor is the chronic use of glucocorticoids, which decreases the secretion of growth hormone and the gonadotrophin pulses, causing pubertal and growth spurt delay. In addition to these effects, they inhibit the replication of osteoblastic lineage cells and stimulate osteoclastogenesis. Conclusion: Insufficient growth and low bone mineral density in pediatric patients with inflammatory bowel disease are complex problems that result from multiple factors including chronic inflammation, malnutrition, decreased physical activity, late puberty, genetic susceptibility, and immunosuppressive therapies, such as glucocorticoids. Resumo: Objetivo: Revisar a fisiopatologia e os métodos de avaliação do crescimento linear e densidade mineral óssea em crianças e adolescentes com diagnóstico de doença inflamatória intestinal. Fontes dos dados: Revisão narrativa a partir de pesquisa nas bases de dados PubMed e Scopus por meio de busca ativa dos termos inflammatory bowel disease, growth, failure to thrive, bone health, bone mineral density, children e adolescents nos últimos dez anos e com busca nos campos título, resumo ou palavra‐chave. Resumo dos achados: As doenças inflamatórias intestinais com início na infância podem apresentar como parte do quadro clínico atraso do crescimento linear, além de baixa densidade mineral óssea. A presença de processo inflamatório crônico com elevados níveis séricos das citocinas inflamatórias interfere negativamente na velocidade do crescimento e na regulação do metabolismo ósseo, além de aumentar o gasto energético, comprometer a absorção de nutrientes e favorecer perdas proteicas intestinais. Outro fator importante é o uso crônico de glicocorticoides, que diminuem a secreção de hormônio do crescimento e dos pulsos das gonadotrofinas e ocasionam atraso puberal e no estirão do crescimento. Além desses efeitos, inibem a reprodução das células da linhagem osteoblástica e estimulam a osteoclastogênese. Conclusão: A insuficiência do crescimento e a baixa densidade mineral óssea em pacientes pediátricos com doença inflamatória intestinal são problemas complexos e que decorrem de múltiplos fatores, inclusive inflamação crônica, desnutrição, diminuição da atividade física, puberdade tardia, suscetibilidade genética a terapias imunossupressoras, como os glicocorticoides. Keywords: Inflammatory bowel disease, Growth failure, Low bone mineral density, Palavras‐chave: Doença inflamatória intestinal, Insuficiência de crescimento, Baixa densidade mineral óssea